ASSESSMENT OF CYTOGENETIC STATUS AND CYTOTOXICITY OF BUCCAL EPITHELIAL CELLS IN PATIENTS WITH CHRONIC RECCURENT APHTOUS STOMATITIS (World Bulletin of Public Health, 2026)
In the Republic of Uzbekistan, the frequency of chronic recurrent aphthous stomatitis among all diseases of MOP is 6.22% and tends to increase, therefore, the study of the cytogenetic and cytotoxic parameters of buccal epithelium in patients is of undoubted practical interest [5]. The aim of the study was to study the cytogenetic and cytotoxic parameters of buccalepithelium in patients with chronic recurrent aphthous stomatitis. Recurrent aphthous stomatitis accounts for up to 90% of all violations of the integrity of the oral mucosa encountered in dental practice. Thus, a significant excess of cytogenetic and karyological disorders was established in patients with a scarring form of the disease in all periods of chronic recurrent aphthous stomatitis